Differential expression of immune genes of adult honey bee (Apis mellifera) after inoculated by Nosema ceranae - Veeranan Chaimanee (2018)
Nosema ceranae is a microsporidium parasite infecting adult honey bees (Apis mellifera) and is known to affects at both the individual and colony level. In this study, the expression levels were measured for four antimicrobial peptide encoding genes that are associated with bee humoral immunity (defensin, abaecin, apidaecin, and hymenoptaecin), eater gene which is a transmembrane protein involved cellular immunity and gene encoding female-specific protein (vitellogenin) in honey bees when inoculated by N. ceranae. The results showed that four of these genes, defensin, abaecin, apidaecin and hymenoptaecin were significantly down-regulated 3 and 6. days after inoculations. Additionally, antimicrobial peptide expressions did not significantly differ between control and inoculated bees after 12. days post inoculation. Moreover, our results revealed that the mRNA levels of eater and vitellogenin did not differ significantly following N. ceranae inoculation. Therefore, in this study we reaffirmed that N. ceranae infection induces host immunosuppression. © 2012.